Experience of the first brazilian ethical committee - Kipper, Délio; Oliveira, Margareth S. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
On the last decade the ethics on research with human being was establish in our contry. The Resolution n°196/96 of the National Health Council hada significant change in ethics manage in the professions of Health Sciences. The objective of the present article to report the experience of theimplanting and the development of the first Ethics Research Committee created in Brazil. On this article will be exhibited the circuntances that pro-moted on the structure of the Committee at Pontifícia Universidade Católica do Rio Grande do Sul, its goals, its attributions and composition of theactual Committee. It is discussed scopes of the committee and procedures on the evaluation of research protocols, based on documents menssioned atthe Resolution n°196/96 of the National Health Council. It is described the activities developed during 1990 and 2004 are discribed. Its limitationsand relevance for of Brazilian scientific society will be further evaluated.